Arbutin Alleviates the Liver Injury of α-Naphthylisothiocyanate-induced Cholestasis Through Farnesoid X Receptor Activation - Wu, Peijie; Qiao, Ling; Yu, Han; Ming, Hui; Liu, Chao; Wu, Wenjun; Li, Baixue (Frontiers in Cell and Developmental Biology, 2021)
Cholestasis is a kind of stressful syndrome along with liver toxicity, which has been demonstrated to be related to fibrosis, cirrhosis, even cholangiocellular or hepatocellular carcinomas. Cholestasis is caused by the dysregulated metabolism of bile acids that are highly cellular toxicity and synthesized from cholesterol in the liver to undergo enterohepatic circulation. In cholestasis, the accumulation of bile acids in the liver causes biliary and hepatocyte injury, oxidative stress and inflammation. Farnesoid X receptor (FXR) is regarded as a bile acid-activated receptors that regulate a network of genes involved in bile acid metabolism, providing a new therapeutic target to treat cholestatic diseases. Arbutin is a glycosylated hydroquinone isolated from medicinal plants in the genus Arctostaphylos, which has a variety of potentially pharmacological properties, such as anti-inflammatory, anti-hyperlipidemic, anti-viral, anti-hyperglycemic and antioxidant activity. However, the mechanistic contributions of Arbutin to alleviate liver injury of cholestasis, especially its role on bile acid homeostasis via nuclear receptors, have not been fully elucidated. In this study, we demonstrate that Arbutin has a protective effect on α-naphthylisothiocyanate induced cholestasis via up-regulating the levels of FXR and down-stream enzymes associated with bile acid homeostasis, such as bile acid efflux transporter bile salt export pump (Bsep), uptake transporter sodium taurocholate co-transporting polypeptide (Ntcp), and bile acid metabolizing enzymes sulfate transferase 2a1 (Sult2a1) and UDP-glucuronosyltransferase 1a1 (Ugt1a1). Furthermore, the regulation of enzymes related with bile acid homeostasis by Arbutin could be abrogated by FXR silencing in LO-2 cells. In conclusion, a protective influence could be provided by Arbutin to alleviate ANIT-induced hepatotoxicity and cholestasis, which was partly through FXR pathway, suggesting Arbutin might be an effective molecule for the treatment of cholestatic liver diseases.